Research of Accuracy of the Aircraft Position Using the GPS and EGNOS Systems in Air Transport - Kamil Krasuski; Ewelina Kobialka; Marek Grzegorzewski (Communications - Scientific letters of the University of Zilina, 2019)
The article presents and describes results of research in determination of the aircraft positioning accuracy with use of the GPS and EGNOS satellite systems in the air navigation. The article, in particular, makes a comparison of the designated aircraft coordinates in the GPS and EGNOS systems in relation to the reference position, determined from the precision differential RTK-OTF technique. The experimental test was conducted in Slovakia, in the vicinity of Kosice airport. In the test, a trial flight by Cessna aircraft was executed over the village of Bidovce (LZBD) in Slovakia, in East-Central Europe. Within the conducted investigations, the GPS and EGNOS positioning accuracies were determined in real time during an in-flight experimental test. Based on the conducted investigations, it was found that the accuracy of the GPS positioning in the air navigation equals ±10 m throughout the most part of the air test. In the same period the EGNOS positioning accuracy in air navigation is equal to ± 5 m.